2016
DOI: 10.2174/1381612822666161006160524
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Notch as a therapeutic approach for human malignancies

Abstract: The provided evidence confirms the importance of Notch pathway in human malignancies indicating that a strong rationale exists for the development of a Notch-tailored therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Accumulating evidence shows that the Notch signaling pathway is overactive in lung, head and neck, pancreatic, bladder, and prostate cancer [ 18 , 19 , 23 – 26 ]. Furthermore, the high expression levels of Notch receptors and ligands have been associated with a poor prognosis in many malignant tumors [ 17 , 19 , 27 ]. In prostate cancer cells, activation of the Notch signaling pathway has been found to contribute to invasion and metastasis by EMT [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence shows that the Notch signaling pathway is overactive in lung, head and neck, pancreatic, bladder, and prostate cancer [ 18 , 19 , 23 – 26 ]. Furthermore, the high expression levels of Notch receptors and ligands have been associated with a poor prognosis in many malignant tumors [ 17 , 19 , 27 ]. In prostate cancer cells, activation of the Notch signaling pathway has been found to contribute to invasion and metastasis by EMT [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway is known to regulate a series of cellular processes, including cell proliferation, apoptosis, cell cycle, chemoresistance, migration, invasion, and stem cell maintenance [ 17 , 18 ]. Moreover, several studies have reported that Notch expression was upregulated in many human malignancies [ 17 , 19 21 ]. However, the function of Notch in the EMT biological processes of cervical cancer remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Upon ligand binding, two proteolytic cleavages release the intracellular Notch portion (ICN) which translocates to the nucleus and triggers the CSL (CBF1/Su(H)/Lag-1) transcription factor to transactivate the Notch target genes. Many of these genes are positive regulators of proliferation and survival and include c-Myc, Bcl2, HES1 [ 1 ], or are involved in the downstream regulation of anti-apoptotic/proliferative pathways such as AKT, NF-κB, Wnt and others [ 2 ]. Notch signaling has also been reported to play a crucial role in the regulation of stem cell and cancer stem cell renewal [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary diseases are determined by mutation in Notch-related genes resulting in reduced Notch signaling with consequent altered development such as Alagille syndrome, spondylocostal dysostosis [ 4 6 ] and cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) [ 7 ]. Oppositely, Notch-related cancers are more frequently associated to increased Notch activity, indicating an oncogenic role of Notch, although a tumor suppressor effect of Notch signaling has also been reported in a minor number of malignancies [ 2 ]. Notch signaling gain-of-function may be acquired by mutations in Notch receptors that, therefore, result constitutively activated independently from ligand engagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation